Automatization of Real Time GNSS Data Acquisition, Validation, Processing for Water Vapor Estimation NUVEM - Gonçalves, Hugo Valentim Figueira (2016)
In the recent years, Global Navigation Satellite Systems (GNSS), in particular Global Positioning Systems (GPS), have proved their capacity to monitor atmospheric water vapor with an accuracy that is comparable to the accuracy of other conventional meteorological sensors. GNSS has several significant advantages compared to the traditional observational systems, including low operating expense, all-weather operability and high temporal/spatial coverage. As a result, the provision of Zenith Total Delay (ZTD) and derived Precipitable Water Vapor (PWV) from GNSS data has become established as a standard and valid technique. These atmospheric parameters are currently assimilated into regional weather forecast models (Meteo Office UK; Meteo France and German Research Center for Geosciences (GFZ)). However, the accuracy of the near realtime estimates for these values is still in active research issue. This dissertation describes the implementation and testing of the estimation of PWV in near-real time that was carried out at SEGAL in framework of the NUVEM project during 2015-2016. The scheme to estimate the atmospheric parameters (ZTD and PWV) and to deliver them timely to the Portuguese Meteo Office (IPMA - Instituto Português do Mar e da Atmosfera) is described in detail. The focus was on the computational component of the scheme but some studies using the estimated solutions were also necessary to be performed in order to obtain some necessary parameters for the operational phase of the project. The timely estimation of the solutions depends of several processes, which needed to be analysed and optimized separately (but considering always their integration in the full schema), namely: • download of the GNSS data from external providers since the project relies on the data acquired by different GNSS networks in Portugal and Spain. • download of the additional products (orbits and clocks) necessary to process the GNSS data. • retrieve from numerical models the values (temperature & pressure) necessary to convert from ZTD to PWV (done at IPMA). • processing of the GNSS solutions as soon as the data and products were available. • uploading of numerical and graphical solutions to IPMA and to the dedicated website. • redundancy of the system in order to guarantee a maximum operational (online) time. Additional features and improvements can be implemented in the future in order to further optimize the use of GNSS-PWV in Portugal for nowcasting. Nevertheless, the goals were achieved since the NUVEM system is currently running in operational mode at SEGAL providing IPMA with timely PWV estimates that can be used to help the analysis of atmospheric events in near-real time.